2010
DOI: 10.1007/s11745-010-3475-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Monounsaturated Fatty Acids but not Saturated Fatty Acids Preserve the Insulin Signaling Pathway via IRS‐1/PI3K in Rat Skeletal Muscle

Abstract: Saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) show different effects on the development of insulin resistance. In this study, we compared the effect of dietary SFA and MUFA on the insulin signaling pathway in the skeletal muscle of a type 2 diabetic animal model. Twenty-nine-week-old male Otsuka Long-Evans Tokushima fatty (OLETF) rats were randomly divided into three groups and fed one of the following diets for 3 weeks; a normal chow diet, an SFA (lard oil) enriched or a MUFA (olive oil) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Similarly, in a meta-analysis of randomized controlled trials looking at the effects of MUFA on glycemic control in individuals with abnormal glucose metabolism, diets high in MUFA were shown to significantly reduce HbA1c [54]. Human trials and animal studies suggest that MUFA may also be involved in the insulin-signaling pathway by playing a role in membrane translocation of glucose transporters in skeletal muscle, as well as by buffering β-cell hyperactivity and insulin resistance [54][56]. Although our results do not show significant improvements in insulin resistance by HOMA or fasting insulin levels, there were a limited number of trials and a significant amount of heterogeneity present in the primary analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a meta-analysis of randomized controlled trials looking at the effects of MUFA on glycemic control in individuals with abnormal glucose metabolism, diets high in MUFA were shown to significantly reduce HbA1c [54]. Human trials and animal studies suggest that MUFA may also be involved in the insulin-signaling pathway by playing a role in membrane translocation of glucose transporters in skeletal muscle, as well as by buffering β-cell hyperactivity and insulin resistance [54][56]. Although our results do not show significant improvements in insulin resistance by HOMA or fasting insulin levels, there were a limited number of trials and a significant amount of heterogeneity present in the primary analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential mechanisms explaining the effects of MUFA on glycaemic control, membrane translocation of glucose transporter type 4 was decreased in the skeletal muscle of rats being on a diet rich in saturated fat [37]. These changes in the insulin signalling pathway could not have been observed in rats fed a high-MUFA diet.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the insulin signalling pathway could not have been observed in rats fed a high-MUFA diet. The authors concluded that the beneficial effect of dietary MUFA on insulin sensitivity is associated with a conserved IRS-1/PI3 kinase insulin signalling pathway, which was altered by saturated fatty acids [37]. In addition, high levels of adiponectin have been shown to be associated with a reduced risk of T2D [38].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models MUFA improve insulin sensitivity in muscle as compared with saturated fatty acids by a mechanism related to the membrane translocation of GLUT4. 38 In humans, some studies have found a reduction in insulin resistance with diets rich in MUFA 39,40 whereas others have not found this relation 41 or even detected a positive relation between the intake and levels of MUFA and insulin resistance. 42,43 In subjects with high fasting triglyceride concentrations, a high MUFA meal causes a lower postprandial rise of insulin that a meal high in saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%